Leadership for Education for Sustainable Development (ESD) : A Case Study from Postcolonial Pakistan - Shah, Mir Zaman, (Educational Research E-Books Online, Collection 2025., 2025)
This book explores the dynamic interplay between educational leadership, sustainable development, and quality education. Drawing on postcolonial and development theories, it examines the colonial legacies and lingering neocolonial influences on postcolonial Pakistan's development and education. Situated in a close analysis of Aga Khan Schools in Chitral District in Khyber Pakhtunkhwa Province, it analyses the key challenges and opportunities educational leaders face in realising the promise of quality education for all. The author critically engages with the global SDG frameworks and simultaneously examines the locally sensitive strategies educational leaders employ to promote access to quality education for sustainable development (ESD).